2022
DOI: 10.1002/jcu.23244
|View full text |Cite
|
Sign up to set email alerts
|

The impact of medical therapy on left ventricular strain: Current state and future perspectives

Abstract: The speckle tracking strain is becoming a frequently used marker of subclinical left ventricular systolic dysfunction. Despite the wide range of data concerning left ventricular strain variability in the general population and its changes in various pathologic conditions, the information about the impact of medical therapy on left ventricle strain is limited. This article provides an analysis of published studies of left ventricle strain changes in response to different agents and combinations of medical thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 117 publications
0
2
0
Order By: Relevance
“…2,49,[71][72][73][74] As previously noted, these incipient (subclinical) systolic impairments do not present with WMA, thus not being able to be detected with conventional echocardiographic methods. 6,20,75,76 Maseri et al have proposed the concept according to which MVD in patients with CSX is not strictly localized in coronary territory supply of a particular epicardial artery, but is rather distributed throughout the myocardium in a more "scattered" manner. This distribution type of perfusion abnormalities may explain the difficulties in objectifying ischemia by standard noninvasive methods.…”
Section: Two-dimensional Left Ventricular Global Longitudinal Strainmentioning
confidence: 99%
See 1 more Smart Citation
“…2,49,[71][72][73][74] As previously noted, these incipient (subclinical) systolic impairments do not present with WMA, thus not being able to be detected with conventional echocardiographic methods. 6,20,75,76 Maseri et al have proposed the concept according to which MVD in patients with CSX is not strictly localized in coronary territory supply of a particular epicardial artery, but is rather distributed throughout the myocardium in a more "scattered" manner. This distribution type of perfusion abnormalities may explain the difficulties in objectifying ischemia by standard noninvasive methods.…”
Section: Two-dimensional Left Ventricular Global Longitudinal Strainmentioning
confidence: 99%
“…It has been shown that MVD alone, without the presence of an obstructive coronary disease, can compromise myocardial perfusion and lead to LV systolic dysfunction 2,49,71–74 . As previously noted, these incipient (subclinical) systolic impairments do not present with WMA, thus not being able to be detected with conventional echocardiographic methods 6,20,75,76 …”
Section: Introductionmentioning
confidence: 96%